Spatial-Temporal Pattern of Vegetation Net Primary Productivity and Its Natural Driving Factors in Ordos Section of the Yellow River Basin - Xiaoguang Wu; Weiwei Hao; Guohua Qu; Lingyun Yang (Atmosphere)
Weather change has a great impact on vegetation growth restoration and ecosystem service function, resulting in significant changes in vegetation net primary productivity (NPP). Therefore, based on MOD17A3 NPP data and meteorological data, this study used the slope of a one-dimensional linear regression equation, Spearman correlation analysis method, and geographical detector model to reveal the spatial and temporal evolution characteristics of NPP in the Ordos section of the Yellow River Basin from 2000 to 2021 and the impact of weather change on NPP. Results: (1) NPP increased from 25.4 gC/m2 in 2000 to 60.3 gC/m2 in 2021. The NPP of vegetation in the northeastern and southern parts of the study area showed a significant increasing trend. (2) From 2000 to 2021, the evaporation showed a fluctuating downward trend, and the relative humidity, temperature, wind speed, surface temperature, and precipitation showed a fluctuating upward trend. (3) Evaporation is the most important factor hindering the growth of NPP. Precipitation, wind speed, and temperature played an important role in promoting NPP, and the average correlation coefficients were 0.62, 0.33, and 0.15, respectively. Relative humidity and surface temperature can promote NPP, but the effect is not significant. (4) The interaction results showed that the combination of temperature and precipitation, wind speed and precipitation, wind speed and temperature, precipitation and evaporation, and precipitation and relative humidity could effectively improve NPP. The interaction of climatic factors has a significant effect on the change of NPP in the Ordos section of the Yellow River Basin. The results provide a strong reference for ecological protection and restoration, the realization of dual carbon goals, and sustainable development in the Yellow River Basin.